Smart volume tuner for cellular phones. - Kumar, S.
This article proposes the use of a smart volume tuner (SVT) for 2G, 2.5G, and 3G cellular phones based on fuzzy logic for improving voice quality in the presence of background noise. The smart volume tuner makes use of the noise level class information generated by a system for fuzzy pattern classification of background noise. The SVT is personalized by using the audiogram to design the fuzzy rule base. The design and simulation of the SVT is discussed, along with implementation details. The FuzzyControl++ tool is used for the simulation of SVT.
Keywords: FuzzyControl++ tool; Background noise; Cellular phones; Fuzzy logic; Fuzzy pattern classification; Fuzzy set theory; Fuzzy systems; Smart volume tuner; Voice quality